Who Moves to the Countryside, and Why? A Systematic Review of Urban-to-rural Migration - Ocek, Ruya Erkan; Islam, Tolga (KARE PUBL, 2025)
As urban areas face issues such as overcrowding and high living costs, rural destinations are attracting diverse migrant groups seeking alternative lifestyles and improved quality of life. This study aims to provide a comprehensive overview of who these migrants are and what drives their decisions to relocate. Following PRISMA guidelines, we analysed 337 peer- reviewed articles from Scopus and Web of Science databases up to 2024. Our findings reveal that urban-to-rural migrants are a heterogeneous group spanning various ages, educational backgrounds, and socioeconomic statuses. Motivations for migration are multifaceted, encompassing economic factors like lower living costs and entrepreneurial opportunities, as well as non-economic drivers such as community connection and proximity to nature. The COVID-19 pandemic has further influenced these trends, accelerating remote work possibilities and health-related concerns. This review highlights the complexity of urban-to-rural migration, emphasizing its potential impacts on rural community dynamics, economic development, and policy-making.
Keywords: Characteristics of migrants; motivations of migrants; PRISMA method; systematic literature review; urban-to-rural migration; LIFE-STYLE MIGRATION; RETURN MIGRATION; AMENITY MIGRATION; FOOD SOVEREIGNTY; GENTRIFICATION; MIGRANTS; HOME; TOURISM; ENTREPRENEURS; CONTEMPORARY; Public Administration